Student E-learning Satisfaction Madrasah in the Digitalization of Education in the Era of Independent Learning in Demak, Central Java - Merrydian, Siska; Safitri, Alsavira; Ndoluanak, Yofran Hengki; Tjalla, Awaluddin; Wahyuni, Lussy Dwi Utami (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2023)
This research aims to determine satisfaction and the implications for the desire to continue using e-learning among madrasah students in the digitalization of education in the era of independent learning. The population of this study was students at MTsS Bahrul General in Demak who used madrasah e-learning. Sampling was carried out by simple random sampling and obtained a sample of 117 students. The data collection method used was using a questionnaire. The data analysis method uses SEM-PLS. The research results show that student attitudes, e-learning quality, and e-learning flexibility have a positive and significant effect on e-learning satisfaction. E-learning satisfaction has a positive and significant effect on the desire to continue using e-learning.